Pelatihan bagi UMKM dalam Mencapai Inklusi Ekonomi melalui Pembayaran Digital dan Akuntansi Terintegrasi - Fina Ruzika Zaimar; Yulia Yunita Yusuf; Anisatun Humayrah Rais; Kartika Septiary Pratiwi Musa; Nur Alim Bahri (Jurnal Akademik Pengabdian Masyarakat Ichsan Sidrap, 2025)
Economic inclusion serves as a foundation for sustainable economic growth, particularly for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. However, many MSMEs continue to face limitations in banking access, financial record-keeping, and the use of digital technology. This community service program aims to enhance digital literacy, expand access to digital payments, and introduce integrated accounting systems for MSMEs. The program was carried out through training sessions, mentoring, and the direct implementation of digital payment applications and technology-based financial recording systems. The results show an improvement in MSME actors’ understanding of cashless transactions, business operational efficiency, and the quality of their accounting records. Thus, this program contributes to accelerating digital-based economic inclusion at the local level.